(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2025)
One of the important components in the Islamic economic system is zakat. because it plays a role in the equitable distribution of wealth and poverty alleviation. However, zakat management often fails to accommodate local needs, especially in rural areas. This study aims to examine the urgency and effectiveness of decentralization of zakat management in supporting distribution justice, with a case study in Sanah Laok Village, Waru District, Pamekasan Regency. This study uses a qualitative descriptive approach with data collection techniques in the form of interviews, observations, and documentation. This study employs a qualitative descriptive methodology, gathering data through observations, interviews, and documentation, The results of the observation indicate that the distribution of zakat is not through official institutions, but is channeled to local religious figures, this practice causes inequality in distribution, this study recommends decentralization of zakat through the establishment of zakat management institutions to ensure equality, accountability, and social justice.